Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 22826 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is 2488485", { "or" : [ "Country is Mexico", "Country is French Guiana", "Country is Honduras", "Country is Brazil", "Country is Cuba", "Country is Ecuador", "Country is Guyana", "Country is Belize", "Country is Suriname", "Country is Haiti", "Country is Venezuela (Bolivarian Republic of)", "Country is El Salvador", "Country is Guatemala", "Country is Costa Rica", "Country is Bolivia (Plurinational State of)", "Country is Peru", "Country is Colombia", "Country is Panama" ] } ] } The dataset includes 22826 records from 93 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002997-150221044754056/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences